2017
DOI: 10.3892/etm.2017.5087
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‑enhanced ultrasonography features of papillary thyroid carcinoma for predicting cervical lymph node metastasis

Abstract: The present study was performed to evaluate the predictive value of contrast-enhanced ultrasonography (CEUS) for the risk of cervical lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC). Between May 2014 and November 2016, 42 patients who received surgery for suspicious PTCs were enrolled in the present study. Each individual underwent CEUS with conventional ultrasound (US), preoperative US-guided fine needle aspiration and personalized surgery. Subsequently, the microvascular density (MVD) of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…A solid composition has not been shown to be associated with CLNM in previous studies; however, our results showed that it was an independent factor for CLNM. We hypothesized that this may be related to the higher blood flow density in solid lesions compared with mixed lesions, and a higher blood flow density was considered to be correlated with CLNM . The value of color Doppler imaging in the differential diagnosis of benign and malignant thyroid nodules is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A solid composition has not been shown to be associated with CLNM in previous studies; however, our results showed that it was an independent factor for CLNM. We hypothesized that this may be related to the higher blood flow density in solid lesions compared with mixed lesions, and a higher blood flow density was considered to be correlated with CLNM . The value of color Doppler imaging in the differential diagnosis of benign and malignant thyroid nodules is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [14] revealed that the heterogeneous hypoechoic enhancement in PTC was the most valuable in predicting CLNM. On the contrary, Liu et al found that partial hyperenhancement in early ascending CEUS period was significantly higher in LNM + group than that in LNM-group [15]. As angiogenesis plays an important role in the development, growth, and metastases of PTC, it was hypothesized in our previous study [16] that the higher enhancements display at peak time is, the greater the microvascular density in PTC and the greater the possibility of neck LN metastasis may happen.…”
Section: Discussionmentioning
confidence: 76%
“…However, the need for a scoring system that performs better than the separate evaluation of single items is increasingly evident. Many different systems have been created in order to meet this need [ 16 , 17 ]; hypo-echogenicity, irregular margins, and the presence of microcalcifications are acknowledged to be risk factors for malignancy, while the role of intra-nodular vascularization is still debated [ 3 , 22 , 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional ultrasound (US) has proved helpful in the management of these lesions, and several scoring systems with satisfactory accuracy and predictive value are now available [ 3 , 6 , 13 18 ]. While few data are available on the role of contrast-enhanced ultrasound (CEUS) in indeterminate-cytology nodules [ 19 ], its utility in distinguishing benign from malignant thyroid lesions and in the evaluation of cervical lymph nodes has already been proved [ 20 22 ]. Elastosonography is an emerging tool in the field of neck imaging and is particularly useful for the evaluation of thyroid nodules, especially if combined with conventional ultrasound [ 19 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%